Estimation of Neutral Density in Edge Plasma with Double Null Configuration in EAST - 张凌 徐国盛 丁斯晔 高伟 吴振伟 陈颖杰 黄娟 刘晓菊 臧庆 常加峰 张炜 李颖颖 钱金平 (Plasma science & technology, 2011)
In this work, population coefficients of hydrogen＇s n = 3 excited state from the hydrogen collisional-radiative （CR） model, from the data file of DEGAS 2, are used to calculate the photon emissivity coefficients （PECs） of hydrogen Balmer-α （n = 3 →n = 2） （Hα）. The results are compared with the PECs from Atomic Data and Analysis Structure （ADAS） database, and a good agreement is found. A magnetic surface-averaged neutral density profile of typical double-null （DN） plasma in EAST is obtained by using FRANTIC, the 1.5-D fluid transport code. It is found that the sum of integral Dα and Hα emission intensity calculated via the neutral density agrees with the measured results obtained by using the absolutely calibrated multi-channel poloidal photodiode array systems viewing the lower divertor at the last closed flux surface （LCFS）. It is revealed that the typical magnetic surface-averaged neutral density at LCFS is about 3.5×10^16 m^-3 .